El lugar de la categoría de fetichismo en la crítica de la economía política: una crítica a Anselm Jappe - Canales Rengifo, Gino (2023)
Against Anselm Jappe’s interpretation of the commodity fetishism as capitalism’s main contradiction, I argue that his work is afflicted by an oversizing of fetishism as a concept that is both deterministic and reductionist, and that his understanding of contradiction in Marx’s work is simplistic. As an alternative, I offer an interpretation of fetishism, which takes as a starting point the idea that the commodity crystallizes capitalist society’s social relations as well as a defense of contradiction as capitalism’s dynamic engine rather than as a paradoxical point of it.